ADAPTING TO CHANGE: THE EXPERIENCES OF EFL TEACHERS WITH CURRICULUM REFORM - Syarifuddin, Syarifuddin; Hz, Benni Ichsanda Rahman (Universitas Islam Sumatera Utara (UISU), 2023)
In the realization of education, it is necessary to regularly update and revitalize the curriculum due to the dynamic nature of knowledge and evolving educational needs. This applies to the domain of teaching English as a Foreign Language (EFL). However, the process of curriculum reform poses several challenges, particularly for teachers who play a vital role in its implementation. This research aims to explore the difficulties encountered by EFL teachers in adapting to the transition from the Curriculum 13 (K13) to the Kurikulum Merdeka (Independent Curriculum) in Indonesia. Through a phenomenological case study, three EFL teachers in the North Sumatra province share their perspectives and experiences in incorporating the new curriculum into their teaching practices. Despite facing essential obstacles such as limited access to ICT resources and inadequate training, the insights gathered underscore the importance of teachers cultivating creativity and adaptability in their teaching methods. Additionally, the study emphasizes the significance of a serious understanding of the subject matter and the integration of 21st-century skills. The diverse viewpoints presented offer current insights into addressing the challenges associated with the development and implementation of EFL at different levels and in various types of schools.